Effect of different cryopreservation media on human nucleus pulposus cells' viability and trilineage potential. Issue 1 (14th February 2021) - Croft, Andreas S.; Guerrero, Julien; Oswald, Katharina A. C.; Häckel, Sonja; Albers, Christoph E.; Gantenbein, Benjamin
Abstract: Introduction: Low back pain (LBP) is a significant cause of disability in many countries, affecting more than half a billion people worldwide. In the past, progenitor cells have been found within the nucleus pulposus (NP) of the human intervertebral disc (IVD). However, in the context of cell therapy, little is known about the effect of cryopreservation and expansion on here called "heterogenic" human NP cells (hNPCs), and whether commercially available cryopreservation media are more efficient than "commonly used" media in terms of cell viability. Materials: In this study, hNPCs from four trauma patients (age 40.5 ± 14.3 years) and two patients with degenerated IVDs (age 24 and 46 years), undergoing spinal surgery, were collected. To isolate hNPCs, the tissue was digested with a mild two‐step protocol. After subsequent expansion, hNPCs at passages 2‐5 were separated and either cryo‐preserved for 1 week at −150°C or differentiated into osteogenic, adipogenic, or chondrogenic lineages for 21 days. Cryopreservation was performed with five different media to compare their effect on the cell's viability and differentiation potential. Cell viability was determined with flow cytometry using propidium iodide and the trilineage differentiation potential was assessed by quantitative polymerase chain reaction and histological analysis. Results: After 1 week of cryopreservation, the hNPC's cell viability was comparable for all conditions, that is, independent of the cryopreservation medium used (82.3 ± 0.8% of cell viability). Furthermore, hNPCs from trauma patients showed some evidence for adipogenic and chondrogenic differentiation and at lower levels, this and evidence of osteogenic differentiation could be confirmed with hNPCs from degenerated discs. Moreover, cryopreservation did not affect the cell's differentiation potential in the majority of the cases tested. Conclusion: "Commonly used" cryopreservation media seem to perform just as well as commercially available media in terms of cell viability and the overall maintenance of the hNPCs trilineage differentiation potential. Abstract : Human nucleus pulposus cell populations (hNPCs) were isolated, expanded, and then cryo‐preserved at −150°C with one of five different cryopreservation media and/or the cells' trilineage differentiation potential was assessed. The cells' viability did not differ between the cryopreservation media tested and hNPCs showed evidence for osteogenic, adipogenic and chondrogenic differentiation.